Analisis Kinerja Kader Posyandu di Desa Gunong Kleng - Tiara Olivia; Sudarman Sudarman (Journal of Social and Policy Issues, 2022)
This study aims to determine the performance of Posyandu cadres in Gunong Kleng Village in inputting dvia a computer. One form of participation in the health sector is the integrated service post (posyandu), which manages the posyandu are cadres. Posyandu cadres have a very important role because it is a health service. The duties of cadres in posyandu activities are registering, weighing every child or mother who comes at the posyandu, maternal and child services in the MCH book are given to health workers. Integrated service posts (posyandu) also provide convenience to the community in the field of basic health services to ease the decline in maternal and child mortality. In this study, qualitative research methods were used which were carried out while at the Keuchik Office of Gunong Kleng Village, precisely at the time of posyandu activities. Among the informants taken were all posyandu cadres in Gunong Kleng Village. Research data collection techniques taken are observation, interviews, and documentation. Due to the educational history of junior high school and high school cadres, the average cadre cannot operate a computer to input data. They still use how to input data manually and after being inputted manually they take it to a typing service to type it in.